The Role of Chemotherapy in Patients With HER2-Negative Isolated Locoregional Recurrence of Breast Cancer: A Multicenter Retrospective Cohort Study - Lee, Kyoungmin; Sim, Sung Hoon; Kang, Eun Joo; Seo, Jae Hong; Chae, Heejung; Lee, Keun Seok; Kim, Ji-Yeon; Ahn, Jin Seok; Im, Young-Hyuck; Park, Seri; Park, Yeon Hee; Park, In Hae (Frontiers in Oncology, 2021)
Background: The role of chemotherapy for isolated locoregional recurrence (iLRR) of breast cancer has not been firmly established after local therapies. Methods: We performed a multicenter, retrospective analysis to evaluate the clinical implications of chemotherapy in breast cancer patients with HER2-negative iLRR. Results: Of a total of 277 patients, 146 (52.7%) received chemotherapy for iLRR. Median follow-up duration was 56.1months. 86 (31.0%) patients had luminal B-like and 100 (36.1%) had TNBC iLRR. There was a trend of longer disease free survival (DFS) in the chemotherapy group (4-year DFS: 70.4% vs. 59.5%, HR = 0.68, 95% CI 0.45–1.02, log-rank p = 0.059). When adjusted with clinically relevant factors, DFS was significantly prolonged with chemotherapy (adjusted HR = 0.61, 95% CI 0.40–0.94, p = 0.023). Subgroup analyses for DFS showed patients with disease free interval (DFI) <5 years or prior chemotherapy had a benefit from chemotherapy (adjusted HR = 0.57, p = 0.018; adjusted HR = 0.51, p = 0.005, respectively). Regarding the molecular subtypes, a longer DFS with chemotherapy was observed both in luminal B-like (4-year DFS: 77.8% vs. 55.0%, HR = 0.51, 95% CI 0.27–0.99, log-rank p = 0.048) and in TNBC patients (4-year DFS: 61.9% vs. 42.8%, HR = 0.49, 95% CI 0.24–1.02, log-rank p = 0.056), but not in luminal A-like.